2014
DOI: 10.1016/j.neuroimage.2014.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Estimating time-varying brain connectivity networks from functional MRI time series

Abstract: At the forefront of neuroimaging is the understanding of the functional architecture of the human brain. In most applications functional networks are assumed to be stationary, resulting in a single network estimated for the entire time course. However recent results suggest that the connectivity between brain regions is highly non-stationary even at rest. As a result, there is a need for new brain imaging methodologies that comprehensively account for the dynamic nature of functional networks. In this work we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
179
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(182 citation statements)
references
References 64 publications
2
179
0
1
Order By: Relevance
“…6 shows the estimated whole-brain directed connectivity matrices Φ [j] y between ROIs for three distinct states. Only significant connections are shown, tested based on the asymptotic normality of the f-SVAR coefficient estimator in (23), at α = 0.05 with Bonferroni correction. As expected from simulations, the TV-VAR-KM approach produces very noisy estimates for the high-dimensional connectivity matrices.…”
Section: B Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 shows the estimated whole-brain directed connectivity matrices Φ [j] y between ROIs for three distinct states. Only significant connections are shown, tested based on the asymptotic normality of the f-SVAR coefficient estimator in (23), at α = 0.05 with Bonferroni correction. As expected from simulations, the TV-VAR-KM approach produces very noisy estimates for the high-dimensional connectivity matrices.…”
Section: B Resultsmentioning
confidence: 99%
“…. , K. Following [23], the K successive timeblocks were repeated for two cycles to emulate the recurring connectivity states. Thus, the state labels and the corresponding state-dependent VAR coefficient matrices (S t , Φ 2) Benchmark with K-means Clustering: We computed factor-SVAR model-based estimates for the state sequence S t , t = 1, .…”
Section: [J]mentioning
confidence: 99%
“…ADMM is suitable for constrained optimization problems and is being used extensively since past few years [30,31,32,33]. This technique facilitates solution by decomposing the original objective function into multiple objective functions that are easy to solve.…”
Section: Algorithm Designmentioning
confidence: 99%
“…Previous studies have shown the great potential of SICE networks for analyzing brain connectivity patterns [17,18,19,20] and diagnosing brain diseases [21,22,23,24]. For each subject, the SICE method naturally produces a set of connectivity networks by specifying different sparsity regularization parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, at which sparsity level the SICE network should be used for classification becomes a critical issue, because different connectivity patterns could possess different discriminative power. A common practice is to select one sparsity level from this set of networks [20,22,23] and ignore other sparsity levels. However, there are at least two drawbacks with this approach: 1) It does not fully exploit the information contained in these ignored sparsity levels; 2) The selection of the most appropriate sparsity level is usually carried out by multi-fold cross-validation, which often has high computational complexity and becomes unreliable when the sample size is small.…”
Section: Introductionmentioning
confidence: 99%